Incidents in the night. Book one - B., David, 1959- (Uncivilized Books, Publisher, 2013)
"In Incidents in the Night David B. (Epileptic, The Armed Garden) sets out to explore the uncharted territories of overflowing and dusty shelves of Paris' legendary book shops. His journey quickly turns into an obsessive vision quest in pursuit of a mysterious 19th Century journal:Incidents In the Night. Mountains of books become sites of archeological digs as the author excavates layers of myth, fact and fiction in search of the elusive thread that links them all. Along the way he stumbles on fanatical Bonapartists, occult conspiracies and the angel of death"--From publisher's web site.